Дослідження властивостей інженерних цементуючих композитів - Сидор, Н. І.; Sydor, N. I. (Видавництво Львівської політехніки, 2019)
Підвищення фізико-механічних властивостей та тріщиностійкості цементуючих композитів при експлуатації будівель та споруд є актуальною проблемою в інженерній практиці. З цією метою розроблено спеціальний клас дисперсно-армованих матеріалів – інженерні цементуючі композити (engineered cementitious composites – ЕСС). У статті показано, що із застосуванням дисперсних волокон можна збільшити міцність на згин ЕСС на 40 %, а додаткова заміна золи винесення на метакаолін – ще на 23 %. Стандартна міцність на стиск модифікованих цементуючих композитів становить 86,7 МПа. Доведено, що дисперсне армування поліпропіленовою фіброю та часткова заміна золи винесенння метакаоліном підвищує тріщиностійкість композитів, оцінену за критичним коефіцієнтом інтенсивності напружень, через 7 та 28 діб у 1,2 разу порівняно зі складом без метакаоліну. Розроблені інженерні цементуючі композити з добавкою метакаоліну характеризуються зменшенням відкритої пористості на 35 %, умовного коефіцієнта розміру пор у 3,4 разу порівняно з базовим композитом.

Concrete is the most widely used building material due to its versatility, durability and availability of raw materials. With the development of the construction industry requirements to concrete, in particular their strength, are increased. Increasing of the physical and mechanical properties and crack resistance of cementitious composites during the operation of buildings and structures is an actual problem in engineering practice. A special class of fiber reinforced materials – engineered cementitious composites (ECC) has been developed for this purpose. The article shows that the use of polypropylene fibers can increase the flexural strength of the ECC by 40 %. Additional replacement of the fly ash on metakaolin and use of fibers is caused increase of the flexural strength of the ECC by 23 % compared to ECC without metakaolin. The standard compressive strength of modified cementitious composites is 86.7 MPa. After firsts cracking, tensile load-carrying capacity continues to increase, resulting in strain-hardening accompanied by multiple cracking. In order to obtain such behavior ECC is designed in accordance with the micromechanics theory which based on the optimization of component composition and microstructure of the material, taking into account the interaction between the fiber, the cement matrix and the transmission zone of the fiber-matrix material. It is proved that fiber reinforcement with polypropylene fiber and partial replacement of fly ash with metakaolin can increase the crack resistance of composites, estimated at critical intensity of stresses, after 7 and 28 days in 1,2 times compared to the composition without metakaolin. Indicators of strength of building composites are directly related to their structure, which is determined by of porosity. The developed engineered cementitious composites with metakaolin are characterized by a decrease of the open porosity by 35 %, a pore size ratio of 3.4 times compared to the base composites.
Investigation of engineered cementitious composites properties
Keywords: інженерні цементуючі композити; мінеральна добавка; в’язкість руйнування; дисперсне армування; міцність; engineered cementitious composites; mineral additive; crack resistance; fiber reinforcement; strength; 691.535